Increased retention of available nitrogen during thermal drying of solids of digested sewage sludge and manure by acid and zeolite addition. (December 2019) - Liu, Jingna; de Neergaard, Andreas; Jensen, Lars Stoumann
Graphical abstract: Highlights: Thermal drying of manure and sewage sludge digestate solids leads to high NH3 loss. Zeolite significantly increased ammonium-N retention in drying of digestate solids. Acidification with H2 SO4 was even more effective, retaining ammonium-N up to 100%. Combining acidification and zeolite had no synergy effect on N retention. The manure and sludge solids behaved different with respect to N retention and loss. Abstract: Thermal drying is an increasingly common post-treatment for digestate-solids, but prone to N losses via ammonia (NH3 ) volatilization. Acidification with strong acids prior to drying may retain ammonium (NH4 + ) in the solids. Natural zeolites can provide adsorption sites for exchangeable cations as ammonium and porosity for free ammonia, which has the potential to contribute to higher N retention in the dried solids. The present study investigated whether the zeolite addition increases NH4 + -N retention during thermal drying of two digestate solids (manure based, MDS; sewage sludge based, SDS), and whether any synergistic effects of combining acidification with sulfuric acid and the addition of zeolite exist. Operating conditions included four pH levels (non-acidified control, adjusted to 8.0, 7.5, 6.5 with concentrated sulfuric acid), four zeolite addition rates (0%, 1%, 5% and 10%), fixed drying temperature (130 °C) and fixed air ventilation rate (headspace exchange rate of 286 times hour −1 ). Zeolite addition significantly increased NH4 + -N retention from 18.0% of initial NH4 + -N in the non-acidified control up to a maximum of 57.4% for MDS, and from 76.6% to 94.5% for SDS. No positive synergistic effect between acidification and zeolite addition was observed, with acidification being the dominant. Nevertheless, zeolite has the potential to be a safe and easy-to-handle alternative to concentrated sulfuric acid.